POLYSEMANTIZATION PROCESSES IN RUSSIAN AND ENGLISH AS A BASIS FOR THE CONSTRUCTION OF A UNIVERSAL ALGORITHM FOR PREDICTING CONNOTATIVE MEANINGS - Mukhammadieva Shakhzoda Farkhodovna (Scholars Digest Publishing, 2023)
This article is based on the study of lexical polysemy within the framework of semantic theory. It is devoted to the study and comparative analysis of polysemantization processes from the point of view of the development of applied linguistics. The research described in the article is relevant to the further development and improvement of automated text analyzers.
Keywords: polysemy, comparative analysis, connotative meaning, automatic text analysis